1998
DOI: 10.1016/s0002-9440(10)65729-x
|View full text |Cite
|
Sign up to set email alerts
|

MDM-2 Oncoprotein Overexpression, p53 Gene Mutation, and VEGF Up-Regulation in Angiosarcomas

Abstract: The endothelium is one of the largest cellular compartments of the human body and has a high proliferative potential. However , angiosarcomas are among the rarest malignancies. Despite this interesting contradiction , data on growth and angiogenesis control mechanisms of angiosarcomas are scarce. In this study of 19 angiosarcomas and 10 benign vascular control lesions we investigated the sequence and expression of the p53 tumor suppressor gene and the expression of the mdm-2 proto-oncogene , which is a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
115
2
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 35 publications
10
115
2
6
Order By: Relevance
“…15 Therefore, angiosarcomas are very rare, and the genetic and molecular mechanisms involved in the malignant transformation of the endothelium are not well understood. 1 The significance of p53 in endothelial malignancies can be appreciated from the observation that transgenic mice with global homozygous or heterozygous deletion of p53 are predisposed to hemangiosarcomas by up to 23%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Therefore, angiosarcomas are very rare, and the genetic and molecular mechanisms involved in the malignant transformation of the endothelium are not well understood. 1 The significance of p53 in endothelial malignancies can be appreciated from the observation that transgenic mice with global homozygous or heterozygous deletion of p53 are predisposed to hemangiosarcomas by up to 23%.…”
Section: Discussionmentioning
confidence: 99%
“…Both p53 mutations and upregulation of the proto-oncogene Mdm2, which is an upstream negative regulator of p53, have been observed in two-thirds of angiosarcoma patients. 15 Most somatic p53 mutations occur between exons 5 to 9, and the mutational frequency and pattern differ at various tumor anatomical sites. 1 Although p53-deficient mice are primarily predisposed to developing thymic lymphomas (>70%), they also develop hemangiosarcoma with relatively low frequency (8-23%).…”
Section: Introductionmentioning
confidence: 99%
“…10 Also, p53 inhibited VEGF expression and, thus, affected the development of angiogenesis by regulating specificity protein 1 (Sp1) and v-src sarcoma viral oncogene homolog (src) kinase activity. [11][12][13] However, the specific mechanism by which RhoA affects p53 is not established yet. Ubiquitination and degradation of p53 are largely controlled by murine double minute 2 (MDM2), an oncogenic E3 ubiquitin ligase that binds with p53, creating a complex to drive proteasome-mediated p53 degradation.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have reported the possible role of CDKN2A and TP53 in tumor development in a subset of angiosarcomas of soft tissue. [15][16][17][18][19][20]37,[40][41][42] Recently, it has been shown that Ink4/Arf deficiency in mice is associated with the development of angiosarcoma, lymphoma and fibrosarcoma. 43 By global testing, we demonstrate that the TGF-b pathway (TGF-b1/phospho-Smad2/PAI-1) is highly active in angiosarcoma of bone and therefore could have an important role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…12 So far, there are relatively few studies investigating cellular and molecular changes within angiosarcoma of bone. Single-case reports and small studies have shown the possible involvement of cell cycle regulators, such as cyclin D1, 13 and tumor-suppressor genes such as CDKN2A and TP53, 1,[14][15][16][17][18][19][20][21] in sporadic angiosarcoma of skin, soft tissue and visceral angiosarcomas suggesting a possible role in tumorigenesis in a subset of angiosarcomas. Moreover, a subset of angiosarcomas harbor specific genetic alterations based on either their anatomical site or exposure to radiation.…”
mentioning
confidence: 99%